Impact of Public Policies on the Technological Innovation in the Renewable Energy Sector - Sánchez, Saidi Magaly Flores; Segovia, Miguel Alejandro Flores; López, Luis Carlos RodrÃguez (International Journal of Energy Economics and Policy, 2020)
The challenges posed by climate change require that the society reconsider its patterns of production and energy consumption, which is why the innovation in the renewable energy sector is fundamental. For this reason, the participation of the State through actions that promote research, development and dissemination of the technologies in this sector is essential to overcome the technical and economic barriers it faces. This research analyzes the impact of six public policy instruments implemented to promote the technological development of the renewable energy sector: economic instruments, regulatory instruments, policy support, research, information and adaptation, and voluntary approaches; differentiating both among groups of countries according to their level of income as well as among energy sources. Through the implementation of a negative binomial model in a panel data panel setting ranging from 1970 to 2012, the results corroborate the positive impact of the implementation of public policy strategies on the innovative activity of the renewable energy sector. However, the effectiveness of the instruments varies according to the level of the wealth of the country and the energy source analysed. These results can add public policy inputs to promote innovative activity in the sector. Keywords: environmental policy, innovation, patents, renewable energy, technological change. JEL Classifications: Q55, Q58, O34, O38 DOI: https://doi.org/10.32479/ijeep.8864